Социальная сущность корпоративной культуры в условиях экономики знаний - Гуревичев, Маркс Михайлович; Иваницкий, Вадим Дорофеевич; Пономарев, Александр Семенович (НТУ "ХПИ", 2014)
Проанализированы сущность, смысл и структура системного понятия корпоративной культуры. Обоснован выбор средств ее формирования на гуманистической основе в условиях современной экономики знаний и мирового кризиса. Показано отличие смысла понятий общей культуры и цивилизации. Этика и эстетика рассматриваются как центральное ядро общей культуры человечества, этнокультур народов мира, культуры корпорации как социоэкономической группы и, таким образом, поощряемой гуманистическим воспитанием эгокультуры личностей.

Analyzed the nature, meaning and structure of the system concept of corporate culture, as well as the notion of the knowledge economy. The choice of ways, methods and means of its formation on a humanistic basis in today's knowledge economy and global crisis. Displaying distinct sense of general concepts of culture and civilization. Ethics and aesthetics are seen as the central core of the general culture of humanity, ethnic cultures of the peoples of the world, the culture of the corporation as a socio-economic groups and thus fostered humanistic education egoculture personalities. Emphasized the role psychological climate as an important element of corporate culture in the effective functioning of the corporation. Emphasized the need for corporate social responsibility and peer review the risks of innovation.
Social essence corporate culture in a knowledge economy
Keywords: инновации; ответственность социальная; этика; эстетика; гуманизм; цивилизация; этнокультура; эгокультура; климат психологический; corporate culture; knowledge economy; innovation development; social responsibility; ethics; humanism